2023
DOI: 10.1186/s13293-023-00561-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex matters for the enhancement of cognitive training with transcranial direct current stimulation (tDCS)

Simone Weller,
Birgit Derntl,
Christian Plewnia

Abstract: Background Transcranial direct current stimulation (tDCS) can influence brain network activity and associated cognitive and behavioural functions. In addition to the extensive variety in stimulation parameters, numerous biological factors drive these effects, however these are yet poorly understood. Here, we investigate one of the major biological factors by focusing on sex-dependent effects of tDCS on a challenging cognitive control task (adaptive paced auditory serial addition task [PASAT]) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Sex differences in working memory, particularly visuospatial rotation, have been extensively researched, and there is a large body of literature to support the association of male sex with higher proficiency in visuospatial rotation ( Gurvich et al, 2020 ). It is plausible that biological sex is associated with neurodevelopmental differences in the robustness of connectivity within networks relevant to our cognitive training task (see Moore and Johnson, 2020 ) and therefore that sex may mediate response to neuromodulation, as in Weller et al (2023) . As a potential clinical tool for cognitive rehabilitation, it is imperative to ensure that our brain stimulation and training protocol is optimized to be effective for male and female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in working memory, particularly visuospatial rotation, have been extensively researched, and there is a large body of literature to support the association of male sex with higher proficiency in visuospatial rotation ( Gurvich et al, 2020 ). It is plausible that biological sex is associated with neurodevelopmental differences in the robustness of connectivity within networks relevant to our cognitive training task (see Moore and Johnson, 2020 ) and therefore that sex may mediate response to neuromodulation, as in Weller et al (2023) . As a potential clinical tool for cognitive rehabilitation, it is imperative to ensure that our brain stimulation and training protocol is optimized to be effective for male and female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that males and females may respond differently to tDCS in terms of cognitive enhancement, pain perception, mood modulation, and other outcomes. Some studies have reported variations in the degree of response or even opposite effects for males and females [36]. There are anatomical differences in brain structure between males and females.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%